The Usage of Social Media and Political Branding of Public Official during Covid-19 - Silviana Purwanti; Nanang Krisdinanto; Rafika Rezky; Budiman Budiman (The Journal of Society and Media, 2022)
The study examined the use of social media by public officials during the Covid-19 Pandemic, focusing on the Twitter accounts of the Java Province Governor. The accounts were studied as they were associated with four of Indonesia's governors with a high level of activity. The study employed a qualitative method. Data were collected from the given Twitter accounts, which contained pieces related to policies for the handling of the Covid-19 pandemic using the NCapture software. The results of the analysis showed that the four governors seemed to deliberately use social media and Covid-19 issues for various purposes ranging from the use of social media as an instrument of information and communication transparency, an instrument for internal government coordination to an instrument for political branding for 2021 Presidential Election. Based on the result of the analysis of the data obtained from Twitter accounts belonging to the governors of java Province Governor, Jakarta, a conclusion is drawn on account of the use of social media during the Covid-19 pandemic